Seleção de alvos imunogênicos para o desenvolvimento de testes sorológicos no diagnóstico da infecção por Schistosoma mansoni - Ana Cristina Loiola Ruas (2022)
The trematode of the species Schistosoma mansoni is a helminth that causes schistosomiasis mansoni, one of the tropical diseases that concernsthe public health, due to the prevalence of severe forms and the large number of deaths that occur worldwide. Currently, the standard diagnosis used and recommended by the World Health Organization (WHO) is the Kato-Katz parasitological method, which performs well in regions of high endemicity. However, its low sensitivity in studies of low to moderate endemic regions, makes the diagnosis difficult and masks the real prevalence of the parasite, thus interfering in the treatment of those infected and their control. Thus, in this work we aim to select immunogenic targets for the development of a rapid test for the diagnosis of S. mansoni infection. For this, sequences of peptides were selected by bioinformatics, by the analysis of immunogenicity and identity, and then, through the immunobloting technique, pool of infected sera from school age children from an endemic area of the Municipality of Januária in the state of Minas Gerais, pool of sera from the same patients 30 days aftertreatment, , pool of non infectedpatients , and pool of sera from patientsinfected with other helminths, which would present possible cross-reactions to S.mansoni,such as Fasciola hepatica, Taenia solium, Taenia saginata, Hymenolepis nana, Ascaris lumbricoides, Ascaris suum, Ancylostoma duodenale, Necator americanus, Enterobius vermicularis, Strongyloidesestercoralis e Toxocaracanis. Therefore, 22 infected reactive peptides were selected, 15 of these were reactive for the group of S. mansoni infected sera, 2 were selected for the group of patients 30 days after treatment and 5 peptides for both groups simultaneously. In short screening and immunogenic for baseline diagnosis, mansoni can produce a baseline test for a highly sensitive serological method with ease of use. Presenting us with a great perspective for diagnosis and, as a consequence, efficient treatment and greater infection control in endemic areas.